PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE ROUND TABLE UNTUK MENINGKATKAN PARTISIPASI DAN PRESTASI BELAJAR SISWA - Nur Elfawati; Johanes Sapri (UNIB Press, 2022)
This study aims to describe the application of the round table cooperative learning model to increase participation and learning achievement of class XI MIPA students of SMA Negeri 1 Kota Agung, Lahat Regency, South Sumatra. The design of this study used a classroom action research (PTK) model of Kemmis and Mc Taggart and a quasi experiment. The subjects of this study were students of class XI MIPA 1 SMA Negeri 1 Kota Agung in the second semester of the 2020/2021 academic year. The number of students for the PTK class is 30 people, the experimental class is 30 people, and the control class is 30 people. The data collection technique used the observation sheet and the learning result test, while the data analysis technique used the average score and the t-test. The results showed that the application of the round table cooperative learning model can increase participation, learning achievement, and effectively improve student learning outcomes in the subject of English class XI MIPA SMA Negeri 1 Kota Agung. The implication of the results of this study is if teachers want to increase participation. and student achievement in English subjects, a round table cooperative learning model can be used